Efficacy of a Native Microbial Starter in Promoting Table Olive Fermentation: An Industrial-Scale Trial at Controlled and Ambient Temperature - Marco Campus; Francesco Corrias; Alberto Angioni; Nicola Arru; Piergiorgio Sedda; Margherita Addis; Myriam Fiori; Antonio Paba; Luigi Chessa; Roberta Comunian (Foods, 2025)
This study evaluated a multi-strain starter culture’s impact on the industrial-scale fermentation of “Tonda di Cagliari” table olives, comparing processes at ambient versus controlled (23–25 °C) temperatures. Controlled fermentation accelerated acidification, yielding lower pH levels, higher lactic acid bacteria (LAB) counts, and better control over Enterobacteriaceae. Starter inoculation ensured the attainment of safe pH levels (<4.2) even at ambient temperature, while uninoculated samples did not reach safe pH levels under those conditions (>4.5 in non-inoculated samples). Regardless of processing temperature, starter-inoculated olives consistently yielded higher final concentrations of hydroxytyrosol (719.2 and 762.9 mg/kg inoculated, 480.7 and 326 mg/kg non-inoculated). Total phenolic content in olives remained higher throughout the fermentation process at the controlled temperature (3138 and 2112 mg/kg ambient temperature, 3458 and 3622 mg/kg controlled temperature). Olives maintained at controlled (higher) temperatures exhibited lower final moisture content and significantly reduced lipid content. While texture profiles were primarily affected by temperature, sensory acceptability was significantly influenced by both the starter inoculation and the fermentation temperature. These findings indicate that using microbial starters can potentially lower energy costs associated with heating processing rooms, particularly during colder seasons, while still ensuring food safety and enhancing nutraceutical value. Although the faster fermentation rate at controlled temperature did not substantially shorten overall marketing time, the starter eliminates the necessity for heating facilities to achieve a food-safe pH within a reasonable timeframe.